Redefining digital divide in Malaysian higher education the case of Covid-19 / Mia Emily Abd Rahim and Emma Marini Abd Rahim - Abd Rahim, Mia Emily; Abd Rahim, Emma Marini (2021)
The article highlights the key issues surrounding internet access in education, its relation to higher learning and major internet service providers in Malaysia. It addresses these constructs particularly in the span of the COVID-19 pandemic and thus, giving an insight into what post COVID-19 might hold for them. This article adapts a monograph by Ismael Peña-López (2010) which describes a comprehensive approach to the phenomenon of the digital divide and digital access based on Marc Raboy and Mark Warschauer's research. It reviews and synthesizes a literature on existing glitches in internet access and the trend of internet usage among tertiary students. As a result, it creates a gap that is still unattended for too long until an insistence becomes the ultimate force of change. The article aspires direct future research based on a set of propositions drawn from different aspects of these key issues spanning over the pre-pandemic years and how it changes the course of internet usage